Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Kecamatan Pamulang Tangerang Selatan - Agung Permadi; Angga Juanda (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstrak. This study aims to analyze the effect of leadership style and organizational culture on employee performance at the Pamulang Subdistrict Office. The research method used is quantitative descriptive research, which is research with data collection through questionnaires and expressed in numerical form involving 69 employees. The results of this study indicate that there is a partial influence between Leadership Style (X1) and Employee Performance (Y) with a t-value of 11.505 > t-table 1.996, therefore Ho1 is rejected and Ha1 is accepted, with a simple linear regression equation of Y = 7.737 + 0.794 (X1). The correlation value of RX1 is 0.815, and Leadership Style contributes 66.4% to Employee Performance, with the remaining 33.6% influenced by other factors. There is a partial influence between Organizational Culture (X2) and Employee Performance (Y) with a t-value of 12.363 > t-table 1.996, so Ho2 is rejected and Ha2 is accepted, with a simple linear regression equation of Y = 6.449 + 0.827 (X2). The correlation value of RX2 is 0.834, and Organizational Culture contributes 69.5% to Employee Performance, with the remaining 30.5% influenced by other factors. There is a simultaneous influence between Leadership Style (X1) and Organizational Culture (X2) on Employee Performance (Y) with a calculated F value of 80.675 > F table 3.14, or a Sig value of 0.000 < 0.05, so Ho3 is rejected and Ha3 is accepted. The multiple linear regression equation is Y = 5.765 + 0.301 (X1) + 0.545 (X2). The correlation value of RX12 0.842 and Leadership Style and Organizational Culture contributed 71% to Employee Performance, with the remaining 29% influenced by other factors. Keywords: Leadership Style, Organizational Culture, Employee Performance.